Home based Factors and Educational Wastage inPublic Secondary Schools in Machakos County - Musangi, Sylvia; Mulwa, David; Migosi, Joash; Kamau, Leonard M (International Journal of Humanities and Social Science, 2017)
This study sought to determine the influence of school-based factors on educational wastage in public secondary school in Kathiani Sub-county, Machakos. A descriptive survey research design was use. The study was carried out in all 31 public secondary schools in Kathiani Sub-county, Machakos County. The target population of the study was 31 principals, 59 form four class teachers, the Sub-county director of education, 10 drop outs and 10 repeaters of secondary level of education in Kathiani Sub-county. All 31 principals were purposefully selected and one class teacher in each school was randomly selected. Data was collected using interview schedules for drop outs and questionnaires for form four class teachers, repeaters, Sub-county director of education and principals. Data was analysed using both descriptive and inferential methods. Quantitative data collected using questionnaires was analysed by the use of descriptive statistics and Chi-square statistical procedure using the Statistical Package for Social Sciences (SPSS version 20). Descriptive statistics that were used in this study include frequencies and mean. The hypothesis was tested using the chi-square test, at a significance level of 0.05. The findings of the study show that there is a statistically significant association between school-based factors and educational wastage in public secondary schools in Kathiani Sub-county. The chi square results for curriculum overload is χ2 (4) =25.44, P=0.000. The results for staffing were χ2 (3) = 26.579, p-value= 0.000. School fees results were χ2 (4) = 27.649 and p-value= 0.000. The results for management support were χ2 (3) =27.140, p=0.000, distance to school results were χ2 (4) =26.070, p=0.000. Results for availability of teaching and learning facilities χ2 (4) =27.123, p=0.000 while results for school fees were χ2 (4) =27.649, p=0.000. In all these cases the P- values were less than 0.05 significance level, meaning they are all significant influencers of educational wastage.
Keywords: Educational wastage; Public Secondary School; Education; School-based factor